The Size Distribution of Farms and International Productivity Differences - Adamopoulos, Tasso; Restuccia, Diego (American Economic Review, 2014)
We study the determinants of differences in farm size across countries and their impact on agricultural and aggregate productivity using a quantitative sectoral model featuring a distribution of farms. Measured aggregate factors (capital, land, economy-wide productivity) account for one-quarter of the observed differences in farm size and productivity. Policies and institutions that misallocate resources across farms have the potential to account for the remaining differences. Exploiting within-country variation in crop-specific price distortions and their correlation with farm size, we construct a cross-country measure of farm-size distortions which together with aggregate factors accounts for one-half of the cross-country differences in size and productivity. (JEL D24, J24, J43, L11, O13, Q12, Q18)